GOOGLE TRANSLATEâ€™S PERFORMANCE IN TRANSLATING A SHORT STORY FROM INDONESIAN INTO ENGLISH - Rahayu, Luh Gede Novita (LPPM Universitas Dhyana Pura, 2020)
[09:49, 10/9/2020] +62 822-4766-2050: ABSTRACT[09:50, 10/9/2020] +62 822-4766-2050: This study is aimed to assess the performance of Google Translate (GT) in translating a short story from Indonesian into English. A short story entitled â€œBabi Milik Sukro Buntingâ€ by Putu Supartika was the object of this study. Documentation method was applied in collecting the data, meanwhile descriptive qualitative method was applied in analyzing the data. The theory applied in assessing the performance of GT was the error classification proposed by Vilar (2006) and supported by Newmark V diagram (1988). With regard to the analysis, all errors were found except incorrect form. Incorrect words and missing words were the dominant errors, meanwhile unknown word and word order were the minor errors found the data. The output of GT was mostly source language emphasis. Moreover, one sentence could have more than one error. In the case of incorrect word, the errors were mostly caused by polysemy, homonymy, and idiom. On the other hand, the missing of content word, article and determiner were the cause of the missing of word error. Another errors were also found in the data, such as wrong translation of pronoun â€œdiaâ€ and suffix â€“nya to encode possessiveness. Keywords: Machine translation, error classification, short story[09:50, 10/9/2020] +62 822-4766-2050: ABSTRAK[09:50, 10/9/2020] +62 822-4766-2050: Penelitian ini bertujuan untuk menilai kinerja Google Translate (GT) dalam menerjemahkan sebuah cerita pendek.Â Objek penelitian ini adalah cerita pendek yang berjudul â€œBabi Milik Sukro Buntingâ€ dikarang oleh Putu Supartika. Metode dokumentasi digunakan untuk mengumpulkan data, sedangkan metode deskriptif kualitatif digunakan untuk menganalisa data. Teori yang digunakan untuk menilai kinerja GT dalam penelitian ini dikemukakan oleh Vilar (2006) tentang klasifikasi kesalahan dan didukung oleh diagram V yang dikemukakan oleh Newmark (1988). Hasil penelitian menunjukkan bahwa semua kesalahan ditemukan kecuali incorrect form. Incorrect word dan missing word adalah kesalahan yang mendominasi, sedangkan unknown word dan word order adalah kesalahan yang sedikit ditemukan pada data. Hasil terjemahan oleh GT sebagain besar menyesuaikan bentuk bahasa sumber. Selain itu, satu kalimat bisa memiliki lebih dari satu kesalahan. Terjemahan kata yang salah biasanya disebabkan oleh polisemi, homonim, dan idiom. Di sisi lain, hilangnya kata inti, article dan determiner merupakan penyebab kesalahan pada kategori missing word. Kesalahan lain juga ditemukan pada data, seperti terjemahan yang salah dari kata ganti